Innovation in the energy sector: the role of fossil fuels and developing economies - Brutschin, Elina; Fleig, Andreas (Energy policy, 2016)
This paper analyzes the effects of fossil fuel rents on R&D expenditures and patent grants in the field of energy-related technology. We argue that an increasing share of fossil fuel rents lessens the innovation of new energy technologies. We consider a sample of countries beyond the common selection of OECD members and investigate innovation efforts in the energy sector of 116 countries from 1980 to 2012. We observe the gradually growing influence of resource-abundant countries on global R&D expenditures and find that increasing fossil fuel rents have a negative effect on patent grants. This study contributes to the ongoing debate concerning the potential effects of resource abundance. More importantly, it increases our understanding of innovation activities within the energy sector and further underscores the need to extend future research to countries that have not been taken into account thus far.